The Future of the Finance Workforce: How Microsoft Copilot May Reshape Roles and Skillsets - Jarunde, Nikhil (International Journal of Finance, 2024)
Purpose: Artificial intelligence (AI) is rapidly advancing, with tools like Microsoft Copilot poised to significantly change the workplace. This paper examines the potential impact of Copilot adoption on the finance workforce. Methodology: It analyzes which financial tasks may be susceptible to automation through Copilot's capabilities and identifies the emerging skills that will be crucial for finance professionals to remain competitive in an AI-driven landscape. Findings: This research provides insights for educators, policymakers, and finance professionals seeking to prepare for the future of work in the finance sector. Unique contribution to theory, policy and practice: In essence, the future of the finance workforce will be characterized by a dynamic interplay between automation, skill evolution, and ethical considerations. By embracing the transformative potential of Microsoft Copilot and cultivating the necessary skillsets, finance professionals can seize opportunities for innovation, drive value creation, and navigate the evolving landscape of finance with confidence and resilience.